The Effect of Discovery Learning with Youtube Media on Student Learning Outucomes on the Materials Environmental Change - Lisna Hayati; Purwati Kuswarini Suprapto; Vita Meylani (Bioedukasi: Jurnal Pendidikan Biologi, 2024)
YouTube media can be utilized and implemented in learning at school by using technological capabilities in accordance with the times. Learning that uses the discovery learning model is more meaningful if collaborated with YouTube media. This study aims to determine the effect of the discovery learning model using YouTube media on students' cognitive learning outcomes on environmental change material in class X MIPA SMA Negeri 1 Rancah Ciamis in the 2022/2023 academic year. The research method used was a quasi-experiment with a nonequivalent pretest-posttest control design. The population in this study were all students of class X MIPA SMA Negeri 1 Rancah consisting of four classes with a total of 152 students. The samples used were X MIPA 2 class as an experimental class totaling 37 students and X MIPA 1 class as a control class totaling 38 students. The sampling technique was carried out by purposive sampling. Data collection techniques in the form of learning achievement tests totaling 30 questions. The instrument used is a learning outcome test on environmental change material. The data analysis technique used an independent t-test whose results obtained a significant value of 0.000 <0.05, so that there was an effect of the discovery learning model with YouTube media on student learning outcomes on environmental change material in class X MIPA SMA Negeri 1 Rancah in the 2022/2020 academic year. It is hoped that in further learning can use YouTube media to improve better student learning outcomes.